THE INFLUENCE OF UTAUT FACTORS ON E-RETENTION WITH E-SATISFACTION AS MEDIATING VARIABLE IN E-LEARNING - Fibria Indriati; Priyanka Agustina (Faculty of Economics and Business, Hasanuddin University, 2018)
Factors on Unified Theory of Acceptance and Use of Technology (UTAUT) are factors derived from UTAUT technology acceptance model, which is used to describe the factors that influence the acceptance of individuals on the implementation of a new technology in the enterprise. This study aimed to analyze the influence of UTAUT factors on E-retention with E-satisfaction as mediating variable. This study uses a quantitative approach with the total samples. The results showed that: (1) Performance Expectancy influences E-retention significantly, (2) Effort Expectancy influences E-retention significantly, (3) Social Influence influences E-retention not significantly, (4) Facilitating Conditions influences E-retention significantly, (5) E-satisfaction influences E-retention significantly, and (6) UTAUT Factors influence E-retention with E-satisfaction as mediating variable. However, the bigger impact is shown through the influence of UTAUT Factors on E-retention directly without going through the E-satisfaction.Â